Budesonide/Formoterol Anti-Inflammatory Reliever and Maintenance or Fluticasone Propionate/Salmeterol Plus as-Needed, Short-Acting β2 Agonist: Real-World Effectiveness in patients Without Optimally Controlled asthma (REACT) Study [Corrigendum] - Cheng SL; Ho ML; Lai YF; Wang HC; Hsu JY; Liu SF; Huang MS; Lee CH; Lin CH; Hang LW; Liu YC; Yang KY; et al. (Dove Medical Press, 2021)
Cheng SL, Ho ML, Lai YF, et al. Drug Des Devel Ther. 2020;14:5441–5450.The authors have advised there is an error in the formatting of the paper title on page 5441, the title “Budesonide/Formoterol Anti-Inflammatory Reliever and Maintenance or Fluticasone Propionate/Salmeterol Plus As-Needed, Short-Acting β2 Agonist: Real-World Effectiveness in pAtients without Optimally Controlled asThma (REACT) Study” should read “Budesonide/Formoterol Anti-Inflammatory Reliever and Maintenance or Fluticasone Propionate/Salmeterol Plus As-Needed, Short-Acting β2 Agonist: Real-world Effectiveness in pAtients without optimally Controlled asThma (REACT) Study”.The authors have also advised the affiliation list on page 5441 is incorrect.  Read the original article